Perancangan dan Pembuatan Visual Novel Sejarah L.M.U. Nurtanio Berbasis Android - Sri Sutjiningtyas; Suharjanto Utomo; Hernawati Hernawati; Rendi Kurniawan (FKOM UNIKU, 2024)
Air Vice Marshal (Anm.) Nurtanio Pringgoadisuryo is an Indonesian aviation hero who remains largely unknown to the younger generation. To raise awareness about him, an engaging and interactive application is required. A Visual Novel can serve as an ideal medium to introduce or preserve the legacy of Air Vice Marshal (Anm.) Nurtanio. The historical Visual Novel about L.M.U Nurtanio was developed using Ren’Py software, a tool for creating visual novels with a simplified version of the Python programming language. The application development followed the Multimedia Development Life Cycle (MDLC), which includes the stages of Concept, Design, Material Collection, Assembly, Testing, and Distribution. This application is accessible on Android-based devices. The design and development of this Android-based historical Visual Novel about L.M.U Nurtanio provide a more engaging and interactive learning medium for Android users.